Low-smoke halogen-free material for energy storage line and production process of low-smoke halogen-free material
By using EVA resin and crosslinking promoter in cable materials, combined with the dispersion of silane coupling agent, the mechanical properties degradation caused by hydroxide flame retardant is solved, and higher tensile strength and oil resistance are achieved, which is suitable for high-end cable products.
Patent Information
- Application Number
- CN202411610676.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-28
AI Technical Summary
Due to the large addition of hydroxide flame retardants in existing cable materials, the overall mechanical properties of the material have been greatly affected, making it difficult to meet the requirements of high-end cable products.
EVA resin is used as the main resin component, and triallyl isocyanurate is added as the crosslinking promoter, and silane coupling agent is selected as the dispersant. Through the synergistic effect of the crosslinking of EVA resin and the dispersant, the tensile strength and oil resistance of the material are improved.
The tensile strength and oil resistance of low-smoke halogen-free materials for energy storage wires are improved, which can better meet the needs of high-end cable products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable materials, and more specifically, to a low-smoke halogen-free material for energy storage lines and a production process thereof. Background Art
[0002] Cable material, also known as cable sheath material, is an important component of power cables. Due to the actual need for fire prevention, flame retardants are generally added to cable materials. Among traditional flame retardants, halogen-containing flame retardants have always dominated due to their high flame retardant efficiency, good processing performance, and low price. Although the flame retardant effect of halogen-containing flame retardants is good, cables with halogen-containing flame retardants will produce toxic and harmful hydrogen chloride smoke in a fire, which can easily cause suffocation and death of people at the fire scene, and hydrogen halide gas will also cause irreversible damage to some high-value electronic equipment. Therefore, halogen-free flame retardants have begun to gradually replace halogen-containing flame retardants, and the market size of halogen-free flame retardant cable materials has also increased year by year.
[0003] In the related technology, there is a low-temperature, oil-resistant, low-smoke, halogen-free flame-retardant polyolefin cable material, which includes the following components in parts by weight: 100 parts of base resin, 130-170 parts of flame retardant, 1-5 parts of lubricant, and 0.5-3 parts of antioxidant; the base resin includes the following components in parts by weight: 30-90 parts of MLLDPE resin, 10-40 parts of POE resin, and 5-30 parts of interfacial compatibilizer; MLLDPE is a metallocene-catalyzed polyethylene product in which the third monomer is hexene, octene, butene, propylene or any two of them copolymerized with ethylene; the interfacial compatibilizer is a maleic anhydride graft of a copolymer of ethylene and a monomer selected from vinyl acetate, methyl acrylate, propylene, butene, hexene or octene, and the flame retardant is a hydroxide flame retardant.
[0004] Regarding the above-mentioned related technologies, the inventors believe that although the cable materials in the related technologies have improved the low-temperature performance and oil resistance of the materials to a certain extent, due to the large amount of hydroxide flame retardants added, the overall mechanical properties of the materials have been greatly affected, making it difficult to meet the requirements of high-end cable products. Summary of the invention
[0005] In the related art, due to the large amount of hydroxide flame retardant added, the overall mechanical properties of the cable material are greatly affected, making it difficult to fully meet the requirements of high-end cable products. In order to improve this defect, the present application provides a low-smoke halogen-free material for energy storage cables and its production process.
[0006] In the first aspect, the present application provides a low-smoke halogen-free material for energy storage lines, which adopts the following technical solution: A low-smoke halogen-free material for an energy storage cable comprises the following components in parts by weight: 18-22 parts of EVA resin, 7-9 parts of POE resin, 6-8 parts of mLLDPE resin, 4-6 parts of a compatibilizer, 0.5-1.5 parts of a lubricant, 45-55 parts of a flame retardant, 4-6 parts of a flame retardant synergist, 0.3-0.5 parts of a masterbatch, 0.6-0.8 parts of a dispersant, 0.25-0.35 parts of a cross-linking accelerator, and 0.6-1.4 parts of an antioxidant; the cross-linking accelerator comprises triallyl isocyanurate, the dispersant comprises a silane coupling agent, and the flame retardant comprises magnesium hydroxide and aluminum hydroxide.
[0007] By adopting the above technical scheme, the present application selects EVA resin as the main resin component, adds triallyl isocyanurate as a cross-linking promoter, and also selects a silane coupling agent as a dispersant. The addition of the dispersant can promote the uniform dispersion of the flame retardant and reduce the negative impact of the flame retardant on the overall mechanical properties of the low-smoke halogen-free material for energy storage lines. Under the conditions of irradiation cross-linking, the molecular chains of the EVA resin can be cross-linked and form a three-dimensional network structure, and TAIC can increase the concentration of cross-linking active points in this process, thereby further increasing the cross-linking degree of the EVA resin. The formation of a three-dimensional network structure limits the mobility of the EVA resin and other components, making the low-smoke halogen-free material for energy storage lines less prone to fracture and damage as a whole, and also helps to reduce the swelling and deformation of the EVA resin in solvent oil, thereby overcoming the defect of poor oil resistance of the EVA resin, so that components such as POE resin, mLLDPE resin, and compatibilizer can more fully improve the overall oil resistance of the material. With the coordinated cooperation of EVA resin, cross-linking promoter, dispersant, flame retardant and other components, the low-smoke halogen-free material for energy storage line of the present application can have a more ideal tensile strength, and the oil resistance is also improved to a certain extent, so it can better meet the needs of high-end cable products.
[0008] Preferably, the flame retardant synergist comprises magnesium aluminum double hydroxide, and the magnesium aluminum double hydroxide is prepared according to the following method: (1) mixing magnesium nitrate and aluminum nitrate and adding them to water to dissolve to obtain a salt solution for later use; adding an intercalant to water to dissolve to obtain an intercalant solution for later use; the intercalant includes sodium dodecyl sulfate; (2) adding the salt solution to the intercalation agent solution under nitrogen protection, and adding sodium hydroxide solution to adjust the pH, and then continuing to perform hydrothermal crystallization treatment under nitrogen atmosphere, and finally centrifugation, and drying the obtained solid to obtain magnesium aluminum double hydroxide.
[0009] By adopting the above technical scheme, the present application uses magnesium nitrate as a magnesium source, aluminum nitrate as an aluminum source, and sodium dodecyl sulfate as an intercalation agent to synthesize magnesium aluminum double hydroxide by coprecipitation. Magnesium aluminum double hydroxide has a lamellar structure, and under the action of the intercalation agent, the exfoliation effect of the lamellar structure is good. In addition to its own flame retardant effect, magnesium aluminum double hydroxide can also improve the dispersion effect of aluminum hydroxide and magnesium hydroxide, two flame retardants, through its lamellar structure, reduce the agglomeration of flame retardants, and reduce the negative impact of flame retardants on the overall mechanical properties of the material, which helps to improve the tensile strength of low-smoke halogen-free materials for energy storage lines.
[0010] Preferably, the dispersant further comprises fatty acid.
[0011] By adopting the above technical scheme, the present application selects fatty acid as a dispersant on the basis of the silane coupling agent. The carboxyl group of the fatty acid can be adsorbed on the surface of aluminum hydroxide and magnesium hydroxide, two flame retardants, so that the surface of aluminum hydroxide and magnesium hydroxide carries a certain amount of organic chain segments, thereby improving the compatibility between aluminum hydroxide, magnesium hydroxide and the resin component, reducing the negative impact of the flame retardant on the overall mechanical properties of the material, and helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0012] Preferably, the fatty acid comprises unsaturated fatty acid.
[0013] By adopting the above technical solution, the unsaturated fatty acid molecules have double bonds and can be cross-linked with the EVA resin under irradiation. At the same time, the carboxyl group of the unsaturated fatty acid can be adsorbed on the surface of the hydroxide flame retardant. Under the action of unsaturated fatty acids, the EVA resin can be indirectly combined with the hydroxide flame retardant, which improves the compatibility between the hydroxide flame retardant and the EVA resin, and the hydroxide flame retardant can also reinforce the network structure, thus helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0014] Preferably, the unsaturated fatty acid contains 3-5 carbon-carbon double bonds in its molecule.
[0015] By adopting the above technical solution, when the unsaturated fatty acid molecule contains 3-5 carbon-carbon double bonds, the unsaturated fatty acid molecule can be more fully cross-linked with the EVA resin, which helps to improve the tensile strength of the low-smoke halogen-free material for energy storage cables.
[0016] Preferably, the silane coupling agent has a carbon-carbon double bond in its molecule.
[0017] By adopting the above technical solution, the present application further limits the silane coupling agent to have a carbon-carbon double bond in the molecule. In this case, while the silane coupling agent is combined with the hydroxide flame retardant, a carbon-carbon double bond is also introduced to the surface of the hydroxide flame retardant. Through radiation cross-linking, a new covalent bond can be formed between this part of the carbon-carbon double bond and the EVA resin, fully realizing the indirect combination of the hydroxide flame retardant and the EVA resin, thereby improving the compatibility between aluminum hydroxide, magnesium hydroxide and the resin component, reducing the negative impact of the flame retardant on the overall mechanical properties of the material, and helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0018] Preferably, the flame retardant further comprises magnesium carbonate fiber, and the magnesium carbonate fiber is prepared according to the following method: (1) using magnesium sulfate heptahydrate and potassium carbonate as solutes to prepare aqueous solutions for later use; (2) Mixing magnesium sulfate solution and polyethylene glycol to obtain a mixed solution, adding potassium carbonate solution dropwise to the mixed solution, stirring evenly and then aging the mixed solution, centrifuging and washing the mixed solution after aging, and drying the mixed solution to obtain magnesium carbonate fibers.
[0019] By adopting the above technical solution, the present application uses magnesium sulfate heptahydrate and potassium carbonate as raw materials, polyethylene glycol as a structure directing agent, and adopts a coprecipitation method to prepare magnesium carbonate fiber. In addition to being able to play a flame retardant role, magnesium carbonate fiber can also play a role in transferring stress in low-smoke halogen-free materials for energy storage cables, which helps to alleviate local stress concentration, and thus can improve the tensile strength of low-smoke halogen-free materials for energy storage cables.
[0020] Preferably, in the method for preparing the magnesium carbonate fiber, the concentration of the magnesium sulfate solution is 0.8-1.1 mol / L.
[0021] By adopting the above technical solution, the present application preferably considers the concentration range of the magnesium sulfate solution, which helps to improve the dispersion effect of the magnesium carbonate fiber.
[0022] Preferably, in the method for preparing the magnesium carbonate fiber, the amount of polyethylene glycol used is 25-35% by weight of the magnesium sulfate heptahydrate.
[0023] By adopting the above technical solution, the present application optimizes the dosage range of polyethylene glycol, which helps to improve the dispersion effect of magnesium carbonate fiber.
[0024] In a second aspect, the present application provides a production process of low-smoke halogen-free materials for energy storage lines, which adopts the following technical solution.
[0025] A production process of low-smoke halogen-free material for energy storage wires, comprising the following steps: (1) EVA resin, POE resin, mLLDPE resin, compatibilizer, lubricant, flame retardant, flame retardant synergist, masterbatch, dispersant, crosslinking accelerator, and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded through a single screw, and then air-cooled hot pelletizing and cyclone separator cooling, and finally screened using a vibrating screen to obtain low-smoke halogen-free material for energy storage lines.
[0026] By adopting the above technical scheme, the method of the present application sequentially carries out batching, internal kneading, mixing, extrusion, pelletizing, cooling and screening, and finally obtains low-smoke halogen-free material for energy storage line.
[0027] In summary, this application has the following beneficial effects: 1. This application uses EVA resin as the main resin component, adds triallyl isocyanurate as a crosslinking accelerator, and also selects a silane coupling agent as a dispersant. With the coordinated cooperation of EVA resin, crosslinking accelerator, dispersant, flame retardant and other components, the low-smoke halogen-free material for energy storage cables in this application can have a more ideal tensile strength, and the oil resistance is also improved to a certain extent, so it can better meet the needs of high-end cable products.
[0028] 2. In the present application, fatty acids are preferred as dispersants, and unsaturated fatty acids are further preferred. Under the action of unsaturated fatty acids, EVA resin can be indirectly combined with hydroxide flame retardants, thereby improving the compatibility between the hydroxide flame retardant and the EVA resin. The hydroxide flame retardant can also reinforce the network structure, thereby helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0029] 3. The present application uses magnesium sulfate heptahydrate and potassium carbonate as raw materials, polyethylene glycol as a structure directing agent, and a coprecipitation method to prepare magnesium carbonate fiber. In addition to being able to play a flame retardant role, magnesium carbonate fiber can also play a role in transferring stress in low-smoke halogen-free materials for energy storage cables, which helps to alleviate local stress concentration, and thus can improve the tensile strength of low-smoke halogen-free materials for energy storage cables. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0031] Preparation example of magnesium aluminum double hydroxide The following is an explanation using Preparation Example 1.
[0032] Preparation Example 1 In this preparation example, magnesium aluminum double hydroxide was prepared according to the following method: (1) 30 mmol of magnesium nitrate and 10 mmol of aluminum nitrate were mixed and added to 50 mL of water to dissolve to obtain a salt solution for later use; 20 mmol of intercalating agent sodium dodecyl sulfate was added to 100 mL of water to dissolve to obtain an intercalating agent solution for later use; (2) Under nitrogen protection, the salt solution is added to the intercalation agent solution at a rate of 300 mL / h, and the pH value is adjusted to 10 by adding sodium hydroxide solution. Then, the solution is subjected to hydrothermal crystallization treatment at 80° C. for 8 h in a nitrogen atmosphere. Finally, the solution is centrifuged and the obtained solid is dried to obtain magnesium aluminum double hydroxide.
[0033] Preparation example of magnesium carbonate fiber The following is an explanation using Preparation Example 2.
[0034] Preparation Example 2 In this preparation example, magnesium carbonate fiber was prepared according to the following method: (1) using magnesium sulfate heptahydrate and potassium carbonate as solutes, respectively, to prepare magnesium sulfate aqueous solution and potassium carbonate aqueous solution for standby use; in this step, the concentration of the magnesium sulfate aqueous solution is 0.6 mol / L, and the molar ratio of potassium carbonate to magnesium sulfate heptahydrate is 1.1:1; (2) Mixing magnesium sulfate solution and polyethylene glycol (PEG600) to obtain a mixed solution, adding potassium carbonate solution dropwise to the mixed solution, continuing to stir for 60 minutes and then aging for 2 hours, centrifugally washing after aging, and drying to obtain magnesium carbonate fiber; in this step, the amount of polyethylene glycol added is 20% of the weight of the magnesium sulfate heptahydrate used in step (1).
[0035] Preparation Example 3 The difference between this preparation example and preparation example 2 is that the concentration of the magnesium sulfate solution is 0.8 mol / L.
[0036] Preparation Example 4 The difference between this preparation example and preparation example 2 is that the concentration of the magnesium sulfate solution is 1.0 mol / L.
[0037] Preparation Example 5 The difference between this preparation example and preparation example 2 is that the concentration of the magnesium sulfate solution is 1.1 mol / L.
[0038] Preparation Example 6 The difference between this preparation example and preparation example 5 is that the amount of polyethylene glycol used is 25% of the weight of the magnesium sulfate heptahydrate used in step (1).
[0039] Preparation Example 7 The difference between this preparation example and preparation example 5 is that the amount of polyethylene glycol used is 30% by weight of the magnesium sulfate heptahydrate used in step (1).
[0040] Preparation Example 8 The difference between this preparation example and preparation example 5 is that the amount of polyethylene glycol used is 35% by weight of the magnesium sulfate heptahydrate used in step (1). Example
[0041] Examples 1-5 The following description is given by taking Example 1 as an example.
[0042] Example 1 The present embodiment provides a low-smoke halogen-free material for energy storage lines, including the following components: 18 kg of EVA resin (model 2803), 7 kg of POE resin (model Dow 8200), 6 kg of mLLDPE resin (model SP2040), 4 kg of compatibilizer (EVA2805-g-MAH, MAH grafting rate is 1.2131 wt%), 0.5 kg of lubricant (silicone masterbatch), 45 kg of flame retardant, and 4 kg of flame retardant synergist (prepared according to the method of Preparation Example 1). g, masterbatch (3028 masterbatch) 0.3kg, dispersant 0.6kg, crosslinking accelerator (TAIC) 0.25kg, antioxidant 0.6kg; the crosslinking accelerator is triallyl isocyanurate, the dispersant is silane coupling agent KH560, the flame retardant is a hydroxide flame retardant, the hydroxide flame retardant specifically includes magnesium hydroxide and aluminum hydroxide, magnesium hydroxide and aluminum hydroxide are mixed in a weight ratio of 3:7, and the antioxidant is a mixture of antioxidant 1076 and DLTP in a weight ratio of 1:1.
[0043] This embodiment provides a production process of low-smoke halogen-free material for energy storage wire, comprising the following steps: (1) EVA resin, POE resin, mLLDPE resin, compatibilizer, lubricant, flame retardant, flame retardant synergist, masterbatch, dispersant, crosslinking accelerator, and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded through a single screw, and then air-cooled hot pelletizing and cyclone separator cooling, and finally screened using a vibrating screen to obtain low-smoke halogen-free material for energy storage lines.
[0044] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the low-smoke halogen-free material used in the energy storage line.
[0045] Table 1 Raw material ratio of low smoke halogen-free materials for energy storage line Example 6 The difference between this embodiment and embodiment 5 is that the dispersant is composed of a silane coupling agent and a fatty acid in a weight ratio of 1:1, and the fatty acid is stearic acid.
[0046] Example 7 The difference between this embodiment and embodiment 5 is that the fatty acid in the dispersant is oleic acid.
[0047] Example 8 The difference between this embodiment and embodiment 5 is that the fatty acid in the dispersant is linoleic acid (cis-6,9,12-octadecatrienoic acid).
[0048] Example 9 The difference between this embodiment and embodiment 5 is that the fatty acid in the dispersant is arachidonic acid.
[0049] Example 10 The difference between this embodiment and embodiment 5 is that the fatty acid in the dispersant is docosapentaenoic acid.
[0050] Embodiment 11 The difference between this embodiment and embodiment 10 is that the silane coupling agent in the dispersant is KH172.
[0051] Example 12 The difference between this embodiment and embodiment 11 is that the flame retardant is formed by mixing a hydroxide flame retardant and magnesium carbonate fiber in a weight ratio of 20:1, and the magnesium carbonate fiber is prepared according to the method of Preparation Example 2.
[0052] As shown in Table 2, the difference between Examples 12-18 is that the magnesium carbonate fiber is prepared according to the methods of different preparation examples.
[0053] Table 2 Preparation example of magnesium carbonate fiber production process reference Embodiment 13 The difference between this embodiment and embodiment 1 is that the flame retardant synergist is nano silicon dioxide.
[0054] Comparative Example Comparative Example 1 A low-temperature, oil-resistant, low-smoke, halogen-free flame-retardant polyolefin cable material comprises the following components in parts by weight: 100 parts of a base resin, 150 parts of a flame retardant, 5 parts of a lubricant, and 1.5 parts of an antioxidant; the base resin comprises the following components in parts by weight: 60 parts of an MLLDPE resin (model: SP2040), 25 parts of a POE resin (model: Dow 8200), and 15 parts of an interfacial compatibilizer (maleic anhydride grafted product of an ethylene-hexene copolymer, with a MAH grafting rate of 1.2%); the flame retardant is aluminum hydroxide.
[0055] The cable material production process of this comparative example is: First, the base resin, aluminum hydroxide, polyethylene wax and antioxidant are fully mixed in a high-speed mixer according to the formula, extruded through a co-rotating twin-screw extruder at a processing temperature range of 110°C, pelletized through a grinding and hot cutting machine, conveyed and cooled by a cyclone separator, and finally sieved through a vibrating screen to obtain a finished product of a low-temperature, oil-resistant, low-smoke, halogen-free and flame-retardant polyolefin cable material.
[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that the raw material for preparing the low-smoke halogen-free material for the energy storage line does not include a flame retardant synergist.
[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that the raw material for preparing the low-smoke halogen-free material for the energy storage line does not include a dispersant.
[0058] Comparative Example 4 The difference between this comparative example and Example 1 is that the raw materials for preparing the low-smoke halogen-free material for the energy storage line do not include a cross-linking accelerator.
[0059] Performance testing methods The material to be tested was made into a sample using a flat vulcanizer at 5 MPa and 120° C., and then irradiated and cross-linked at an absorbed dose of 180 kGy to obtain a sample to be tested for later use.
[0060] The tensile strength of the test sample was tested in accordance with the provisions of GB / T 32129-2015 Halogen-free low-smoke flame-retardant cable materials for wires and cables. The tensile strength of Comparative Example 1 was used as a benchmark to calculate the ratio between the tensile strength of each embodiment and the comparative example and the tensile strength of Comparative Example 1, and the ratio was recorded as the relative tensile strength. The results are shown in Table 3.
[0061] The oil resistance test was carried out on the test samples according to GB / T1690-2010 standard. The experimental oil was 3# standard oil (IRM903). Each group of test samples was made into a type II dumbbell bar with a width of 4 mm and a gauge length of 25 mm, immersed in a beaker filled with 3# standard oil, and the temperature was set to (23±2)°C for 168 h. The change rate of the tensile strength before and after oil immersion was tested, and then the tensile strength change rate of Comparative Example 1 was used as a benchmark to calculate the ratio of the tensile strength change rate of each embodiment and comparative example to the tensile strength change rate of Comparative Example 1. The ratio was recorded as the relative strength loss rate. The results are shown in Table 3.
[0062] Table 3 It can be seen from Examples 1-5 and Comparative Example 1 and Table 3 that the relative tensile strengths measured in Examples 1-5 are all higher than those in Comparative Example 1, indicating that with the coordinated cooperation of components such as EVA resin, cross-linking promoter, dispersant, and flame retardant, the low-smoke halogen-free material for energy storage lines of the present application can have a more ideal tensile strength, and the oil resistance is also improved to a certain extent, thereby being able to better meet the needs of high-end cable products.
[0063] Combining Example 1, Comparative Example 2 and Table 3, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 2, indicating that in the absence of the flame retardant synergist magnesium aluminum double hydroxide, Comparative Example 2 cannot fully improve the tensile strength of the material.
[0064] Combining Example 1 and Comparative Example 3 and Table 3, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 3. This is because in the absence of a dispersant, the dispersion effect of aluminum hydroxide and magnesium hydroxide is poor, resulting in a decrease in the mechanical properties of the low-smoke halogen-free material for energy storage cables.
[0065] Combining Example 1 and Comparative Example 4 and Table 3, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 4, and the relative strength loss rate is also lower. This is because TAIC can increase the degree of crosslinking of the EVA resin, making the low-smoke halogen-free material for the energy storage line less prone to fracture and damage as a whole. It also overcomes the defect of poor oil resistance of the EVA resin, allowing components such as POE resin, mLLDPE resin, and compatibilizer to more fully improve the overall oil resistance of the material. Therefore, in the absence of TAIC, Comparative Example 4 not only has a decreased tensile strength, but also has difficulty in improving oil resistance.
[0066] Combining Example 5 and Example 6 with Table 3, it can be seen that the relative tensile strength measured in Example 6 is higher than that in Example 5, indicating that the synergistic effect of the silane coupling agent and the fatty acid improves the compatibility between aluminum hydroxide, magnesium hydroxide and the resin component, reduces the negative impact of the flame retardant on the overall mechanical properties of the material, and improves the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0067] It can be seen from Example 6, Example 7-10 and Table 3 that the relative tensile strength measured in Example 7-10 gradually increases, while the relative loss rate of strength also gradually decreases. This is because under the action of unsaturated fatty acids, the EVA resin can be indirectly combined with the hydroxide flame retardant, which improves the compatibility between the hydroxide flame retardant and the EVA resin, and the hydroxide flame retardant can also reinforce the network structure, thereby helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines, and also reducing the attenuation of tensile strength during oil resistance testing. When the unsaturated fatty acid molecule contains 3-5 carbon-carbon double bonds, the unsaturated fatty acid molecule can be more fully cross-linked with the EVA resin, which helps to further improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0068] Combining Example 10, Example 11 and Table 3, it can be seen that the relative tensile strength measured in Example 11 is higher than that in Example 10, while the relative strength loss rate is lower than that in Example 10. This is because the silane coupling agent combines with the hydroxide flame retardant and introduces a carbon-carbon double bond to the surface of the hydroxide flame retardant. The radiation crosslinking of the carbon-carbon double bond with the EVA resin can promote the indirect combination of the hydroxide flame retardant and the EVA resin, thereby improving the compatibility between aluminum hydroxide, magnesium hydroxide and the resin component, reducing the negative impact of the flame retardant on the overall mechanical properties of the material, and helping to improve the tensile strength of the low-smoke halogen-free material for energy storage lines.
[0069] Combining Example 11, Example 12 and Table 3, it can be seen that the relative tensile strength measured in Example 12 is higher and the relative strength loss rate is lower. This is because in addition to being able to play a flame retardant role, the magnesium carbonate fiber can also play a role in transferring stress in the low-smoke halogen-free material for energy storage cables, which helps to alleviate local stress concentration and thus can improve the tensile strength of the low-smoke halogen-free material for energy storage cables.
[0070] It can be seen from Examples 12-18 and Table 3 that in the method for preparing magnesium carbonate fiber, when the concentration of the magnesium sulfate solution is 0.8-1.1 mol / L, and when the amount of polyethylene glycol is 25-35% of the weight of magnesium sulfate heptahydrate, the tensile strength of the low-smoke halogen-free material for energy storage line is higher, and the tensile strength lost during the oil resistance test is less.
[0071] Combining Example 1, Example 19 and Table 3, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Example 19. This is because the magnesium aluminum double hydroxide in Example 1 can improve the dispersion effect of aluminum hydroxide and magnesium hydroxide, two flame retardants, through the lamellar structure, reduce the agglomeration of the flame retardant, and reduce the negative impact of the flame retardant on the overall mechanical properties of the material, which helps to improve the tensile strength of the low-smoke halogen-free material for energy storage lines. Although the nano-silicon dioxide in Example 19 can also be used as a flame retardant synergist, it is relatively ineffective in improving the dispersion effect of aluminum hydroxide and magnesium hydroxide, resulting in a lower tensile strength measured in Example 19.
[0072] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A low-smoke halogen-free material for energy storage wire, characterized in that: The invention comprises the following components in parts by weight: 18-22 parts of EVA resin, 7-9 parts of POE resin, 6-8 parts of mLLDPE resin, 4-6 parts of compatibilizer, 0.5-1.5 parts of lubricant, 45-55 parts of flame retardant, 4-6 parts of flame retardant synergist, 0.3-0.5 parts of masterbatch, 0.6-0.8 parts of dispersant, 0.25-0.35 parts of crosslinking accelerator and 0.6-1.4 parts of antioxidant; the crosslinking accelerator comprises triallyl isocyanurate, the dispersant comprises a silane coupling agent and the flame retardant comprises magnesium hydroxide and aluminum hydroxide.
2. The low-smoke halogen-free material for energy storage wire according to claim 1, characterized in that: The flame retardant synergist comprises magnesium aluminum double hydroxide, and the magnesium aluminum double hydroxide is prepared according to the following method: (1) Mixing magnesium nitrate and aluminum nitrate and adding them to water to dissolve them to obtain a salt solution for later use; adding an intercalant to water to dissolve them to obtain an intercalant solution for later use; the intercalant includes sodium dodecyl sulfate; (2) Under nitrogen protection, the salt solution is added to the intercalation agent solution and mixed, and sodium hydroxide solution is added to adjust the pH value, and then the solution is subjected to hydrothermal crystallization treatment under nitrogen atmosphere, and finally centrifuged and dried to obtain a magnesium aluminum double hydroxide.
3. The low-smoke halogen-free material for energy storage wire according to claim 2, characterized in that: The dispersant also includes fatty acids.
4. The low-smoke halogen-free material for energy storage wire according to claim 3, characterized in that: The fatty acids include unsaturated fatty acids.
5. The low-smoke halogen-free material for energy storage wire according to claim 4, characterized in that: The unsaturated fatty acid molecules contain 3-5 carbon-carbon double bonds.
6. The low-smoke halogen-free material for energy storage wire according to claim 5, characterized in that: The silane coupling agent has a carbon-carbon double bond in its molecule.
7. The low-smoke halogen-free material for energy storage wire according to claim 2, characterized in that: The flame retardant further comprises magnesium carbonate fiber, and the magnesium carbonate fiber is prepared according to the following method: (1) Using magnesium sulfate heptahydrate and potassium carbonate as solutes, respectively, prepare aqueous solutions for later use; (2) Mixing magnesium sulfate solution and polyethylene glycol to obtain a mixed solution, adding potassium carbonate solution dropwise to the mixed solution, stirring evenly and then aging the mixed solution. After aging, centrifugal washing is performed and magnesium carbonate fibers are obtained after drying.
8. The low-smoke halogen-free material for energy storage wire according to claim 7, characterized in that: In the method for preparing the magnesium carbonate fiber, the concentration of the magnesium sulfate solution is 0.8-1.1 mol / L.
9. The low-smoke halogen-free material for energy storage wire according to claim 8, characterized in that: In the method for preparing the magnesium carbonate fiber, the amount of polyethylene glycol used is 25-35% of the weight of magnesium sulfate heptahydrate.
10. The method for preparing the low-smoke halogen-free material for energy storage wire according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) EVA resin, POE resin, mLLDPE resin, compatibilizer, lubricant, flame retardant, flame retardant synergist, masterbatch, dispersant, cross-linking accelerator and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded by a single screw, and then air-cooled hot pelletized and cooled by a cyclone separator, and finally sieved by a vibrating screen to obtain low-smoke and halogen-free material for energy storage lines.